2006
DOI: 10.2337/diabetes.55.04.06.db05-1076
|View full text |Cite
|
Sign up to set email alerts
|

Clustering of Insulin Resistance With Vascular Dysfunction and Low-Grade Inflammation in Type 2 Diabetes

Abstract: 1Vascular dysfunction, low-grade inflammation, insulin resistance, and impaired fibrinolysis have each been reported to be present in type 2 diabetes, but their relationships, and the role of obesity, have not been investigated. We measured insulin sensitivity (euglycemic clamp), forearm blood flow responses to graded local acetylcholine (Ach) and sodium nitroprusside (SNP) infusions, plasma concentrations of tumor necrosis factor (TNF)-␣, interleukin (IL)-6, von Willebrand factor (vWF), plasminogen activator … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
132
3
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 174 publications
(143 citation statements)
references
References 55 publications
6
132
3
2
Order By: Relevance
“…TNF-␣ levels have been reported to be significantly elevated in insulinresistant type 2 diabetic subjects (39,40). Although First Nation and control women had similar levels of TNF-␣, a weak correlation was found between TNF-␣ and HOMA-IR but only in the First Nation individuals.…”
Section: The Contribution Of Adipose Tissue To Adipokine Levelsmentioning
confidence: 78%
“…TNF-␣ levels have been reported to be significantly elevated in insulinresistant type 2 diabetic subjects (39,40). Although First Nation and control women had similar levels of TNF-␣, a weak correlation was found between TNF-␣ and HOMA-IR but only in the First Nation individuals.…”
Section: The Contribution Of Adipose Tissue To Adipokine Levelsmentioning
confidence: 78%
“…These pro-inflammatory markers also positively correlated with insulin resistance and the features of the metabolic syndrome, in most cases, independently of the degree of obesity [6,7,[12][13][14].…”
Section: Inflammatory Markers In Obesity Metabolic Syndrome and T2dmmentioning
confidence: 84%
“…Using the forearm technique, we have previously shown that EDV is reduced in diabetic patients in proportion to their degree of insulin resistance [46]. Insulin resistance, however, does not cluster with EDV in nondiabetic normotensive participants [47] or in patients with essential hypertension [48].…”
Section: Discussionmentioning
confidence: 97%